Roles of Articles in Agabag, a Dayic Language of North Borneo - Radjaban, Yohanes (Universitas Teknologi Yogyakarta, 2019)
As an article simply plays a syntactic role in a language, it is often overlooked in a linguistic research on syntax (Farrell 2005). If it happens to Austronesian languages like Agabag, it will be a fatal mistake since an article has significant roles (Hudson 1978). The discussion of this paper is aimed at describing the roles of articles in Agabag. Generative-Transformational Approach is applied for the sake of descriptive and explanatory adequacies (Haegeman 1991). All processes of analyses are based on transformational principles, which involve theories of head-modifiers relations, which are also used to describe the structures and patterns of articles in Agabag. The analyses of this research result in some findings. Agabag language has articles which function as a determiner of an NP and become role assigners to the NP. The interpretation of the articles of Agabag is based on their function as a determiner as well as role-assigners to the NP. As a determiner, articles of Agabag are interpreted as ‘this’ and ‘that’. As a role assigner each article is interpreted according to the role it assigns. If agreement between articles and NPs in most languages relies on gender and number, in Agabag it is based on the roles of NP (Radjaban 2013).